Evolution of young protoclusters embedded in dense massive clumps. A new grid of population synthesis SED models and a new set of L/M evolutionary tracks. Issue 4 (2nd April 2019) - Molinari, Sergio; Baldeschi, Adriano; Robitaille, Thomas P; Morales, Esteban F E; Schisano, Eugenio; Traficante, Alessio; Merello, Manuel; Molinaro, Marco; Vitello, Fabio; Sciacca, Eva; Liu, Scige J
Abstract: A grid of 20 millions 3–1100 μm spectral energy distribution (SED) models is presented for synthetic young clusters embedded in dense clumps. The models depend on four primary parameters: the clump mass M clump and dust temperature T dust, the fraction of mass f core locked in dense cores, and the age of the clump t SF . We populate the young stellar object (YSO) clusters using the Kroupa initial mass function and the YSOs SED models grid of Robitaille et al. We conduct extensive testing of SED fitting using a simulated data set and we find that M clump essentially depends on the submillimetre portion of the SED, while T dust is mostly determined from the shape of the SED in the 70–350 μm range. Thanks to the large number of models computed, we verify that the combined analysis of L / M, [8–24] and [24–70] colours removes much of the SEDs f core – t SF degeneracy. The L / M values are particularly useful to diagnose f core . L / M ≤ 1 identifies protoclusters with f core ≤ 0.1 and t SF .6ex aise.65ex 10^5 yr, while L / M .6ex aise.65ex 10 excludes f core ≤ 0.1. We characterize lower limits of L / M where zero-age main sequence (ZAMS) stars are not found in models, and we also find models with L / M ≥10 and no ZAMS stars, in which [8–24] .6ex aise.65ex 0.8± 0.1 independently from M clump, temperature, and luminosity. This is the first set of synthesis SED models suited to model for embedded and unresolved clusters of YSOs. A set of new evolutionary tracks in the L / M diagram is also presented.